1903 Or. Special Laws 106, An Act to Incorporate the City of North Bend, and to Provide a Charter Therefor . . . , § 27, pt. 23. - (:unkn) unknown (My University, 1903)
To regulate the transfer of gunpowder, dynamite, nitro-glycerine, and other combustibles and explosives through the streets§ or alleys of the city[.]
Keywords: GUNPOWDER - TRANSPORTATION